Promoting Agricultural Research and Development to Strengthen Food Security in South Asia - Ghose Bishwajit (International Journal of Agronomy)
This study aims to highlight the status of agricultural R&D in South Asia and contends that creating an effective agricultural research and innovation systems is a vital element to ensure food security in this region. South Asia is home to around one-fourth of mankind and houses the largest proportion of undernourished people in the world. Despite a period of marked economic growth averaging 6% a year over the past two decades, it remains the world's second poorest region contributing a mere 2.2% in global annual GDP. Agriculture is the mainstay of South Asian economy employing around 60% of the total workforce and generating around 20% of total GDP. South Asia has the recognition of being the second most food-insecure region next only to sub-Saharan Africa. Though there is growing evidence that technological innovation has a key role to play in increasing agricultural production and strengthening food security, agricultural research and development (R&D) sector has failed to garner sufficient attention till now. This study also depicts the current situation of food security in South Asia and illustrates how agricultural education and innovation hold the master key to solve the food security issues for the world's most densely populated region.